Analysis of Hepatitis C Virus cis-elements involved in the Initiation of Negative-Strand RNA Synthesis - Malik, Attiya Qadoos; Justus Liebig University Giessen (My University, 2026)
Hepatitis C Virus infects approximately 3 % of the global population. Because infection often remains asymptomatic for long periods, many cases progress unnoticed to severe liver diseases such as cirrhosis, hepatocellular carcinoma or chronic liver failure. HCV possesses a positive-strand RNA genome that replicates via negative-strand RNA intermediate. While many aspects of HCV replication are well studied, comparatively little is known about the cis-acting RNA elements on the positive-strand genome that are involved in the initiation of negative-strand RNA synthesis. Studying negative-strand RNA synthesis poses major technical challenges, particularly due to background signals that obscure accurate detection. The background signals arise from false priming (1) during in vitro-transcription and (2) during reverse transcription due to the strong hairpin structure at the 3´end of the RNA genome and (3) contaminating residual plasmid DNA and transfected RNA that serves as a false template during cDNA synthesis. Furthermore, it is essential to measure negative-strand RNA synthesis uncoupled from other viral processes such as translation and positive-strand RNA replication. To address these challenges, an HCV subgenomic (4th generation) replicon system was developed combined with a highly optimized strand-specific RNA detection assay. The system allows precise detection of newly synthesized negative-strand RNA with negligible background. Template DNA contamination from in vitro-transcribed RNA was (nearly) completely eliminated by two rounds of DNase digestion followed by RNA purification using Monarch kit columns. Total RNA extracted using TRIzol also underwent additional DNase treatments, acidic phenol/chloroform extraction and column-based purification to further enhance RNA quality. To selectively detect RNA new transcribed only after transfection of the replicon, 5EU-labelling was used in combination with Click iT chemistry. The 5EU-labelled nascent RNA was biotinylated, captured using streptavidin beads, and subjected to ten stringent washing steps before analysis by RT-qPCR. High temperature conditions during reverse transcription (65 °C) and qPCR (62 °C) further minimized nonspecific amplification. This approach reduced the background signals from polymerase deficient negative controls to only 0.02 - 0.035 %, representing an approximately 975-fold improvement over earlier methods in the Niepmann laboratory using 1st generation replicon system and conventional RNA purification procedures. Using this highly sensitive platform, the study identified the SLI-II region of the HCV 5´UTR as the minimal essential cis-acting element required for the initiation of negative-strand RNA synthesis. The SLI-III domain, which comprises the IRES region of the HCV 5´UTR, supported about 34.5 % of the overall efficiency of the negative-strand RNA synthesis. In contrast, mutations disrupting binding of eIF3 or the 40S subunit (∆IIIb and mutIIId/e) caused a drastic reduction in negative-strand RNA levels, both in SLI-III as well as in complete 5´UTR construct. These findings underscore the essential role of an intact HCV 5´UTR in genome replication and suggest that recruitment of eIF3 and the small ribosomal 40S subunit positively regulate negative-strand RNA synthesis. Similar to the PCBP2 protein, these factors may bridge the 5´- and 3´-ends of the viral genome, promoting genome circularization. Competitive binding of NS5B dimer or oligomer to the 5´UTR may disrupt this interaction, enabling replication via NS5B binding to the 3´-end. Such interactions may function as a checkpoint determining whether the genome undergoes translation and/or replication. Detection of negative-strand RNA is currently reliable only from 24 hpt onward, and further optimization is required to analyse initiation events at earlier time points.
Keywords: Hepatitis C; Negative-Strand; ddc:570